In Vitro Comparison of Dye Penetration through Four Temporary Restorative Materials - Shahriar Shahi; Mohammad Samiei; Saeed Rahimi; Hossein Nezami (Iranian Association of Endodontists; Iranian Center for Endodontic Research, 2010)
INTRODUCTION: The purpose of this in vitro study was to compare the coronal seal of four temporary filling materials, Coltosol, Zonalin, Zamherir, and Intermediate Restorative Material (IRM) by the India ink dye penetration test. MATERIALS AND METHODS: Endodontic access preparations were prepared in 120 extracted intact human premolars. The teeth were randomly divided into six groups including four experimental and two control groups. The access cavities in each group were sealed with Coltosol, Zonalin, Zamherir, and IRM; subsequently thermocycling was applied for 5-55˚C for 150 cycles. The teeth were immersed in 10% India ink for 72 hours to assess leakage. The teeth were then rinsed, dried, and sectioned mesiodistally and evaluated under a stereomicroscope for dye penetration. Data were analyzed using one-way ANOVA and post hoc Tukey tests. RESULTS: Positive control specimens showed complete dye penetration, while negative controls had no penetration. In the experimental groups, the lowest and highest leakage scores were observed in the Zonalin and Coltosol groups, respectively (P<0.05). There were no statistically significant differences in marginal leakage between Zonalin-Zamherir and Coltosol-IRM groups. CONCLUSION: These results suggest that Zonalin and Zamherir have a superior seal and less micro-leakage into the canals compared to the two other materials.